(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper examines the significance of evaluation and strategy selection in the anti-crisis management of the energy sector industry. In a volatile and rapidly evolving energy industry landscape, making informed choices regarding management strategies becomes crucial for ensuring the efficient and sustainable operation of energy companies. By analyzing the current context and employing relevant theoretical models and concepts, the article provides an overview of key aspects related to the evaluation and strategy selection in the anti-crisis management of the energy sector industry.